2020
DOI: 10.1055/s-0040-1715173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Obesity with External Cephalic Version Success among Women with One Previous Cesarean Delivery

Abstract: Objective Our aim was to assess the correlation of body mass index (BMI) with the success rate of external cephalic version (ECV) among women with one prior cesarean delivery. Study Design A cross-sectional study of pregnant women with one previous cesarean delivery who underwent ECV. The relationship between BMI and success rate of ECV was assessed. Adverse outcomes were also compared between women with an ECV attempt, and women who had a repeat cesarean delivery. Data were extracted from the U.S. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In that study, the BMI of the woman was measured the same day as the version was performed, unlike the present study where the BMI of the woman was determined at the maternity care center in the first trimester. McLaren et al studied a subgroup of women with previous cesarean section and found no correlation between maternal BMI and the outcome of the version 12 . They obtained data from the US Natality Database (generated from birth certificates) from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, the BMI of the woman was measured the same day as the version was performed, unlike the present study where the BMI of the woman was determined at the maternity care center in the first trimester. McLaren et al studied a subgroup of women with previous cesarean section and found no correlation between maternal BMI and the outcome of the version 12 . They obtained data from the US Natality Database (generated from birth certificates) from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The ECV procedure has been evaluated in relation to maternal body mass index (BMI) but results are inconsistent and many questions persist. Burgos et al, and recently Jouzova et al, found no difference in the success rate of ECV according to the BMI of the woman; neither did McLaren et al, whose study population comprised women with a previous cesarean section 10–12 . In contrast, Ben‐Meir et al showed that a BMI over 25 kg/m 2 was a factor associated with an unsuccessful ECV 13 .…”
Section: Introductionmentioning
confidence: 94%
“…Burgos et al, and recently Jouzova et al, found no difference in the success rate of ECV according to the BMI of the woman; neither did McLaren et al, whose study population comprised women with a previous cesarean section. [10][11][12] In contrast, Ben-Meir et al showed that a BMI over 25 kg/m 2 was a factor associated with an unsuccessful ECV. 13 Chaudary et al, Isakov et al, and Correia Costa et al, found that obese women had a lower probability of a successful ECV.…”
Section: Introductionmentioning
confidence: 96%
“…Burgos et al found no difference in success rate based on the BMI of the woman in a Spanish cohort including 500 ECVs from a single center 10. In that study, the BMI of the woman was measured the same day as the version was performed, unlike the present study where the BMI of the woman was determined at the maternity care center in the first trimester.McLaren et al studied a subgroup of women with previous cesarean section and found no correlation between maternal BMI and the outcome of the version 12. They obtained data from the US Natality Database (generated from birth certificates) from 2014 to 2017.According to the flowchart they identified 1.6 million women with a scar and ended up analyzing 2329 ECVs, which might indicate that an absolute majority of women with breech presentation had a repeat cesarean delivery.…”
mentioning
confidence: 99%